Experiments in applied microbiology - Singer, Samuel (Academic Press, 2001)
This is a lab manual intended for use in undergraduate courses and some graduate courses. It contains open-ended experiments to teach applied bacteriology approaches and techniques. Included are the fundamental principles of bacteriology, microbial ecology, bacterial physiology, basic fermentation, and biocontrol. There is no other lab manual of this kind in the market. It breaks new ground in hands-on bacteriology, emphasizing the role of bacteria in both microbiological and macrobiological disciplines.